Platform-Mediated Devotion and Institutionalized Charisma: Digital Rituals of Majelis Rasulullah in Indonesia - Asyathri, Fitria Zahrah (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2026)
Digital religion research has extensively examined online preaching, religious influencers, and changing religious authority, but less attention has been given to how digital platforms mediate collective ritual and reproduce the charisma of deceased religious leaders. This study examines how Majelis Rasulullah SAW uses digital platforms to mediate devotional performance, ritual participation, and the institutionalized charisma of its founder, Habib Munzir Al-Musawa. It employed a qualitative case study based on digital observation and limited offline participant observation conducted from February to May 2026. The digital dataset comprised approximately 130 Instagram posts, content from the organization’s official website, and the YouTube livestream and live-chat interactions associated with the Thirteenth Haul Akbar of Habib Munzir. The data were analyzed thematically using Weber’s concepts of charismatic authority and routinization, Joosse’s concept of charismatic aristocracy, and Campbell’s framework of networked religion. The findings show that the website primarily functions as an informational archive, whereas Instagram facilitates ritual mobilization, logistical coordination, and post-event circulation. YouTube enables geographically dispersed audiences to follow and respond to the ritual synchronously while making religious intermediaries and devotional performances publicly visible. However, engagement metrics and live-chat activity indicate visibility and participation rather than direct evidence of devotion or charismatic recognition. The study argues that Majelis Rasulullah’s digital presence represents selective platformization: official digital channels extend established offline rituals by selecting and circulating event information, ritual images, religious figures, and organizational messages while maintaining institutional control over communication. Platform-mediated charisma is therefore reproduced through commemorative ritual, visible intermediaries, organizational curation, and the convergence of online and offline participation.